Comparison of Outcomes of External Dacryocystorhinostomy and Transcanalicular Laser-Assisted Dacryocystorhinostomy in Patients with Primary Acquired Nasolacrimal Duct Obstruction - Mutlu, Demet; Bayram, Nurettin; Arici, Mustafa Kemal; Ozec, Ayse Vural; Erdogan, Haydar; Toker, Mustafa Ilker (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose This study aimed to compare anatomical and functional outcomes of external dacryocystorhinostomy (EX-DCR) and transcanalicular multidiode laser dacryocystorhinostomy (TDL-DCR) in patients with primary acquired nasolacrimal duct obstruction (PANDO).Methods This study was conducted on 60 eyes of 60 patients with PANDO. The study subjects were randomly divided into two groups. Group 1 included 30 patients who underwent EX-DCR, and group 2 included 30 patients who underwent TDL-DCR. Surgery success rates were determined by patency of the neo-ostium, with free saline flow on irrigation and the absence of epiphora.Results There were 23 women (76.7%) and 7 men (23.3%) with a mean age of 47.33 ± 12.44 years in group 1, and 18 women (60%) and 12 men (40%) with a mean age of 46.2 ± 19.4 years in group 2. There was no significant difference between groups 1 and 2 with respect to age or gender (p = 0.801, p = 0.267, respectively). The mean duration of symptoms was 3.2 years, ranging from 1.5 to 5 years. The mean postoperative follow-up was 12.3 ± 2.44 months. At the end of the follow-up period, the surgery success rates were 96.7% (29/30 eyes) in group 1, and 90% (27/30 eyes) in group 2. There was no statistical difference in the surgery success rates between groups (p = 0.612).Conclusion TDL-DCR is a minimally invasive and safe procedure. The lack of bleeding and incision scar and shorter operation time suggest that TDL-DCR can be a good alternative in PANDO patients.
Keywords: anatomy; orbit; nasolacrimal ducts